NEW RECORD OF DENDRITOBILHARZIA PULVERULENTA (TREMATODA: SCHISTOSOMATIDAE) FROM PAKISTAN. - N. A. Birmani; A. M. Dharejo; M. M. Khan; A. M. Shaikh (Journal of Animal and Plant Sciences, 2013)
During present studies on helminth parasites of black coot, Fulica atra (Gruiformes: Rallidae), in Sindh Province of Pakistan, twelve specimens (eight ♂ and four ♀) of Dendritobilharzia pulverulenta (Braun, 1901) Skrjabin, 1924 were collected from eleven hosts. Male D. pulverulenta were more frequent. This is first record of the genus Dendritobilharzia Skrjabin and Zakharow, 1920 from Pakistan.
Keywords: Dendritobilharzia pulverulenta; Fulica atra; Sindh; Pakistan